Two new marine cyclopinids (Crustacea: Copepoda: Cyclopoida) from interstitial habitats in Korea - Karanovic, Tomislav (Zootaxa, 2021)
Marine cyclopoids, and especially cyclopinids, are poorly studied because their diversity is highest in marginal habitats, such as intertidal interstitial and anchialine caves, or in highly inaccessible abyssal and hadal depths. Two new cyclopinids are described here, both from two different sandy beaches in Korea. Among four species currently recognized in the genus, Heterocyclopina koreaensis sp. nov. is most closely related to H. vietnamensis Pleşa, 1969 from similar habitats in Vietnam. Koreacyclopina wellsi gen. et sp. nov. shares its sexually dimorphic third exopodal segment of the second leg with the Antarctic genus Pseudocyclopina Lang, 1946, but differs from all six known species by numerous features, some of which are observed for the first time within cyclopinids. Both Korean species belong to the family Hemicyclopinidae, but the monophyly of this group has not yet been demonstrated.